Piece of my heart - Clark, Mary Higgins / Burke, Alafair; Burke, Alafair (New York : Simon & Schuster, 2020)
A high-suspense follow-up to the best-selling "You Don't Own Me" finds the nuptials of television producer Laurie Moran and investigative host Alex Buckley nightmarishly upended by the sudden disappearance of Alex's seven-year-old nephew.
Keywords: Television producers and directors -- Fiction; Missing persons -- Investigation -- Fiction; Reality television programs -- Fiction; Suspense fiction; Mystery fiction